Pengembangan Modul Berbasis Kearifan Lokal pada Pembelajaran Tematik untuk Siswa Kelas IV SDN 19 Pasir Tinggi - Sri Tini; Elva Zuleni (Jurnal Halaqah, 2022)
This research was appointed based on the background of developing modules based on local wisdom in thematic learning for fourth grade students at SDN 19 Pasir Tinggi. The teaching materials/modules used by educators are still not based on local wisdom. The discussion of learning materials is still comprehensive and does not link the material being taught with the conditions in the immediate environment of students. As a result, students find it difficult to understand the material being studied. Based on this, a local wisdom-based learning module was developed. Theme 1 The Beauty of Togetherness, sub-theme 1 Cultural diversity of my nation learning 1 and 2. This study aims to produce valid, practical and effective modules to be used as supporting teaching materials/modules for fourth grade elementary school students. . This type of research is development research (R&D) using a 4-D model (define, design, development, disseminate). This research was conducted in a limited number of 10-15 people. Data collection instruments in this study were in the form of module validation sheets (design experts, linguists, and material experts), practicality tests and effectiveness tests. The results of the validation of the development of local wisdom-based modules with four validators were declared very valid, ten students for the practicality test were declared very practical, and ten students for the effectiveness test were also declared very effective. With the level of validity, the validity test results obtained from the percentage of design feasibility (93.18%), language (80.76 %), material I (90.38%) and material II (92.30%). The results of the practicality test for educators get an average value (90.76%) and from the practicality test by students get a value (92.75%) The results of the effectiveness test of ten students get an average value (96%) for learning I and (96%) for study II. Proving that the development of local wisdom-based learning modules in thematic learning for fourth grade students of SDN 19 Pasir Tinggi theme 1 sub-theme 1 learning 1 and 2 is declared valid, practical, and feasible to use.